Purple glove syndrome - Adrianna Szeliga; Dominika Spyt; Mateusz Kasinowicz (Journal of Education, Health and Sport, 2019)
Introduction: Purple glove syndrome is an atypical and adverse reaction to intravenous phenytoin, which is characterized by oedema, pain and a dark purple-bluish discolouration, typically located on an upper extremity. The clinical manifestation of this syndrome occurs in three stages: appearance, progression and resolution of symptoms. PGS develops up to 12 hours after administration of intravenous phenytoin and it disappears in a few weeks or months.